The membrane depolarization and increase intracellular calcium level produced by silver nanoclusters are responsible for bacterial death - Junior Bernardo Molina-Hernandez (Nature Portfolio, 2021)
Abstract This work highlights how our silver ultra nanoclusters (ARGIRIUM-SUNc) hand-made synthesized, are very useful as a bactericide and anti-biofilm agent. The Argirium-SUNc effective antibacterial concentrations are very low (< 1 ppm) as compared to the corresponding values reported in the literature. Different bacterial defense mechanisms are observed dependent on ARGIRIUM-SUNc concentrations. Biochemical investigations (volatilome) have been performed to understand the pathways involved in cell death. By using fluorescence techniques and cell viability measurements we show, for the first time, that membrane depolarization and calcium intracellular level are both primary events in bacteria death. The ARGIRIUM-SUNc determined eradication of different biofilm at a concentration as low as 0.6 ppm. This suggests that the effect of the nanoparticles follows a common mechanism in different bacteria. It is highly probable that the chemical constitution of the crosslinks could be a key target in the disrupting mechanism of our nanoparticles. Since the biofilms and their constituents are essential for bacterial survival in contact with humans, the silver nanoparticles represent a logical target for new antibacterial treatments.